Dynamic output feedback linearizing control of saturated induction motors with torque per ampere ratio maximization - Peresada, Sergei; Kovbasa, Serhii; Dymko, Serhii; Bozhko, Serhiy (2016)
The paper presents a novel maximum torque per Ampere (MTA) controller for induction motor (IM) drives. The proposed controller exploits the concept of direct (observer based) field orientation and guarantees asymptotic torque tracking of smooth reference trajectories and maximizes the torque per Ampere ratio when the developed torque is constant or slowly varying. A dynamic output-feedback linearizing technique is employed for the torque subsystem design. In order to improve torque tracking accuracy a motor magnetizing curve is taken into account during MTA optimization and controller design.